P032 Alone but supported with an innovative HIV self-testing app: qualitative results from a large cohort study in south africa. (14th July 2019) - Janssen, Ricky; Engel, Nora; Esmail, Aliasgar; Oelofse, Suzette; Smallwood, Megan; Daher, Jana; Marathe, Gayatri; Karatzas, Nicolaos; Dheda, Keertan; Pai, Nitika Pant
Abstract : Background: HIV self-testing (HIV-ST) has the potential to positively impact HIV test access, uptake and early diagnosis. Its widespread adoption could change the nature of how and where patients access HIV testing. But concerns remain regarding test conduct, provision and nature of counselling, and support offered during/after HIV-ST. This study investigated an oral HIV-ST application (app) based strategy (an oral self-test with a mobile phone/tablet app), that offered HIV pre-test counselling, risk staging, test conduct/interpretation, and linkages to care. We aimed to identify if and how the app provided counseling and support during/after HIV-ST and how this strategy might impact test access in the South African context. Methods: We conducted a qualitative study nested within an observational cohort study (November 2016 – May 2018) with concurrent comparators, in the township populations of Cape Town, South Africa. Participants could choose between supervised HIV-ST/unsupervised HIV-ST in private spaces around the clinic, and unsupervised HIV-ST at home. Qualitative data were collected from study participants and study staff using 33 semi-structured interviews, one focus group discussion, and observation notes. Audio files and notes were transcribed and themes were developed iteratively. NVIVO 9 (QSR International) was used during analysis. Results: Compared to conventional testing, participants perceived the app-based HIV-ST strategy as convenient. The convenience to test anywhere gave participants more control in choosing whom they included in the testing process. It addressed stigma, social visibility and privacy concerns by letting testers answer sensitive questions and receive their results privately. Future concerns centered on affordability, smartphone access, and usability in older and rural users. Conclusion: The innovative app-based strategy addressed multiple HIV testing barriers by making testing convenient and private. The flexible access and support offered by the strategy could aid in expanding access and linkages for HIV-ST and related co-infections in South Africa and beyond. Disclosure: No significant relationships.